The jekyll and hyde of our drinking: Event specific drinking, intervention, and prevention - Riordan, B.; Flett, J.; Lam, Tina; Conner, T.; Scarf, D. (2016)
We often look at alcohol use as an average, simplifying data down to how many drinks an individual consumes during a typical week or month. Although an average is a good starting point, it provides little information on the way(s) individuals drink. For example, an average of 14 drinks per week may reflect an individual having a couple of drinks each day of the week or 14 drinks every Friday night. Indeed, weekly averages can make it look like we drink like Dr. Jekyll while disguising our Mr. Hyde. One factor known to bring out our Hyde is an event. In fact, events are associated with both an increase in alcohol use and alcohol-related harm. Although the majority of research on events has been conducted in university students (e.g., Orientation Week, 21st birthdays), recent research suggest that event specific drinking is not just a student phenomenon. In this chapter we will explore a number of events associated with excessive drinking and outline the harm experienced during these events. In addition, we discuss approaches our group and others have used to reduce event specific drinking in a student population.